Potency of the Sabin inactivated poliovirus vaccine (sIPV) after exposure to freezing temperatures in cold chains. Issue 8 (2nd August 2020) - Cai, Wei; Ping, Ling; Shen, Wuling; Liu, Jing; Zhang, Ming; Zhou, Jian; Peng, Jia; Wang, Mingqing; Zhu, Yun; Ji, Guang; Wang, Xiaoyu; Ji, Qiuyan; et al.
ABSTRACT: With more demand for Sabin inactivated poliovirus vaccines (sIPVs) to support the global polio eradication effort worldwide, data regarding the potency characteristics of sIPV after exposure to freezing temperatures are urgently required. In the present study, the sIPVs were stored at −20°C for 24 h, 1 week, and 2 weeks in the freezer or in a vaccine carrier for 1 or 3 freeze-thaw cycle to evaluate the effect mediated by freezing temperatures that may be encountered during routine storage and transfer. The in vitro potency was then determined by a D-antigen enzyme-linked immunosorbent assay, and the in vivo potency was evaluated in Wistar rats. In the in vitro study for freezer storage groups, the D-antigen contents for all three types decreased and were lower than the release specifications after storing at −20°C for 2 weeks. After storing at −20°C for 1 week, the D-antigen contents for types I and III in combined group of a total of 45 vials, and for type II in the specific lot groups containing 15 vials decreased, but were within the release specifications. Moreover, no significant change in in vivo potency was observed. For vaccine carrier transfer groups, the D-antigen contents did not decrease after 1 freeze-thaw cycle; in contrast, it decreased, but no significant in vivo potency loss was observed after 3 freeze-thaw cycles. These results suggest that it may be possible to retain sufficient sIPV potency after short periods of freezing or freeze-thawing during transport.